2010
DOI: 10.1128/jcm.01709-09
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Etiology of Travelers' Diarrhea in Mexico, Guatemala, and India: Importance of Enterotoxigenic Bacteroides fragilis and Arcobacter Species

Abstract: This study examined established enteric pathogens, Arcobacter species and enterotoxigenic Bacteroides fragilis (ETBF), in 201 U.S. and European travelers with acute diarrhea acquired in Mexico, Guatemala, and India. Arcobacter butzleri and ETBF were detected in 8% and 7% of diarrhea cases, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(75 citation statements)
references
References 23 publications
(19 reference statements)
7
64
3
1
Order By: Relevance
“…Prevalence of A. butzleri in human stools. We observed that the overall prevalence of A. butzleri in human stools was 60%, which is much higher than the rates of 25% or less reported by others (9,12,41,42). We attribute the high rate of A. butzleri detection in the current study to our use of primers designed and validated for maximum efficiency in complex matrices.…”
Section: Discussioncontrasting
confidence: 42%
“…Prevalence of A. butzleri in human stools. We observed that the overall prevalence of A. butzleri in human stools was 60%, which is much higher than the rates of 25% or less reported by others (9,12,41,42). We attribute the high rate of A. butzleri detection in the current study to our use of primers designed and validated for maximum efficiency in complex matrices.…”
Section: Discussioncontrasting
confidence: 42%
“…were detected in 6.66% (2/30) of diarrhoeic human stools. In India, the detection rate of Arcobacter in diarrhoeic humans have ranged from 2% to 15% (Jiang et al, 2010;Mohan et al, 2014 andRamees et al, 2014). Asymptomatic carriage of Arcobacter in veterinary students (8.0%, 2/25) and farm workers (13.3%, 4/30) was also observed in the present study.…”
Section: Resultssupporting
confidence: 64%
“…In that study, one third of the patients with A. butzleri infections presented with diarrhea, and all of them presented with abdominal pain and nausea (18). Arcobacter butzleri has also been detected in travelers' diarrhea at a rate of 8% (16/201 stool specimens) in U.S. and European travelers returning from Mexico, Guatemala, and India (19). However, in that study, other organisms were also concomitantly isolated from stool samples from 13 of these patients, confounding the role of Arcobacter as the causative agent of the symptoms in these patients (19).…”
Section: Case Reportmentioning
confidence: 99%
“…Arcobacter butzleri has also been detected in travelers' diarrhea at a rate of 8% (16/201 stool specimens) in U.S. and European travelers returning from Mexico, Guatemala, and India (19). However, in that study, other organisms were also concomitantly isolated from stool samples from 13 of these patients, confounding the role of Arcobacter as the causative agent of the symptoms in these patients (19). A. butzleri has also been implicated in severe and persistent diarrhea in immunocompromised adults (16).…”
Section: Case Reportmentioning
confidence: 99%